Wish - Smith, Jake 1974- (Thorndike, Maine : Center Point Large Print, 2014)
"A father wishes his 9-year-old son would be well enough to play catch. The son wishes to see his father play in a major league baseball game. They all pray for a successful bone marrow transplant before cancer ends the boy's life, but first, they need to find a donor"--
Keywords: Detroit Tigers (Baseball team) -- Fiction; Fathers and sons -- Fiction; Sons -- Fiction -- Death; Last words -- Fiction; Large type books; Baseball stories; Christian fiction